Prevalence of internet addiction and its relationship with disordered eating among medical college students in south India: a cross-sectional study - B Lakshmi Dorai; Sanila Sara Alex; C Pradeep (Kerala Journal of Psychiatry, 2021)
Background: The easy availability of various gadgets with the provision of faster internet at affordable prices has exponentially increased internet usage in the past few years. This study aimed to estimate the prevalence of internet addiction and describe its association with disordered eating in medical college students. Methods: This cross-sectional study was conducted on 300 medical college students in south India. After obtaining ethical clearance and informed consent, students were given a questionnaire containing sociodemographic variables, Young's Internet Addiction Test (IAT), and Eating Attitudes Test questionnaires (EAT). Descriptive analysis was carried out by mean and standard deviation for quantitative variables, frequency, and proportion for categorical variables.  Categorical outcomes were compared between study groups using the chi-square test. Univariate binary logistic regression analysis was performed to test the association between the variables. Results: The prevalence of internet addiction was 46.7% in this study. Disordered eating was found to be 12.3% in medical students. Internet addiction was observed to be more in the younger age group.  (P <0.001) A significant association was obtained between internet addiction and disordered eating. (P <0.05). Conclusion: Nearly half of the medical students in this study were addicted to the internet, and disordered eating was also high among medical students. A closer look into the aspects like internet addiction and eating disorders is required, as these may silently impact the life and productivity of the budding doctors.